Gamification in Fiqh Instruction at the Madrasah Level: Mitigating Student Learning Burnout through Digital Interactive Platforms - Anggilika Rahmatullah; Andi Wulan Purnama (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore in depth the implementation of a gamification approach using the Wordwall platform in Fiqh instruction and its role in addressing the phenomenon of student learning burnout at the madrasah level. Fiqh instruction, which is often characterized by a normative-textual orientation, tends to rely on conventional lecture-based methods that may trigger psychological fatigue, reduced engagement, and decreased intrinsic motivation among students. This study adopts an interpretive paradigm with a descriptive qualitative case study design to capture the organic dynamics of classroom interaction and the transformation of learning experiences through gamification. Data were collected through participatory observation, in-depth interviews with the Fiqh teacher, the madrasah principal, and eighth-grade students, as well as document analysis to triangulate findings. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings reveal that the integration of game elements such as points, levels, challenges, instant feedback, and visual rewards through the Wordwall platform significantly contributes to reducing students’ learning burnout. This approach enhances intrinsic motivation, fosters active participation, and alleviates academic stress. Furthermore, gamification transforms the classroom environment from a passive, teacher-centered, and text-dominated setting into a more dynamic, interactive, and student-centered learning space. The study underscores the potential of digital gamification as an innovative pedagogical strategy in Islamic education to create meaningful, engaging, and psychologically supportive learning experiences.